Application of prechop technique in phacoemulsification for cataract patients with highly liquefied vitreous: a retrospective study - Jing Zhao; Zhouyue Li; Yu Liu; Xiaotong Han; Shengsong Huang (BMC Ophthalmology, 2022)
Abstract Background Phacoemulsification using phaco-chop technique has many challenging features in cataract patients with highly liquefied vitreous. This study aimed to compare the intraoperative parameters and safety between prechop technique and traditional phaco-chop in phacoemulsification for these patients. Methods A total of 54 eyes of 54 patients with high myopia-related or post-vitrectomy cataract that underwent phacoemulsification combined with intraocular lens implantation were included in this retrospective study. Of them, 25 eyes that received manual prechop were included in the prechop group, and 29 eyes with best match of age, axial length and nuclear opalescence (NO) that received standardized phaco-chop were included as the control group. The intraoperative complications and surgery parameters were compared between groups. Results No surgical complications were observed in the prechop group, while 2 eyes with posterior capsular rupture and 1 eye with a broken ciliary zonule (10.3%) were found in the control group. There was no significant difference in phaco time, average energy, and cumulative dissipated energy (CDE) between groups (all P > 0.05), but for hard nuclear cataracts with NO grading ≥ 5, prechop group required less phaco time (P = 0.008) and CDE (P = 0.029). There were significant correlations between phaco time vs. NO (r = 0.762 vs. 0.581, both P < 0.005) and CDE vs. NO (r = 0.717 vs. 0.668, both P < 0.001) in the prechop group and control group, respectively. Conclusions The prechop technique which seemed to have less intraoperative complications, reduced phaco time and CDE compared to standardized phaco-chop might be a good alternative for cataract patients with highly liquefied or vitrectomized vitreous, especially those with hard nuclear cataracts.